Accurate Age Estimation Using 14C Content in Japanese Human Teeth. Issue 3 (20th February 2017) - Kunita, Keisuke; Nakamura, Toshio; Kato, Kazuo
Abstract: We investigated age estimation of persons using 45 Japanese human teeth that consisted of mainly the third molar. We measured the radiocarbon content in tooth enamel hydroxyapatite from the crown as well as those in collagen and bioapatite in the root of the same tooth. Age estimations from tooth enamel apatite yielded an absolute age shift of 1.7±1.4 yr from the true age. This value suggests that estimating the age of Japanese people from tooth enamel is as accurate as the previous studies conducted in Europe and the USA. The 14 C analysis of roots suggested that bioapatite is formed slightly later than collagen in the same tooth roots. The appropriate formation age ranges suggested by the tooth enamel analysis can be optimized and confirmed by using the additional F 14 C values of the root samples. We also noticed a characteristic trend of enamel δ 13 C values in comparison with the formation ages of the crowns of the teeth. The δ 13 C value tends to increase gradually from –13.0‰ to –11.5‰ from the 1960s to the 1970s, probably being caused by changes in the Japanese diet. This trend may support the selection of proper tooth formation age as supplemental data in addition to 14 C content analyses.